Regulation and Function of Versatile Aerobic and Anaerobic Respiratory Metabolism in Pseudomonas aeruginosa - Arai, Hiroyuki (Frontiers in Microbiology, 2011)
Pseudomonas aeruginosa is a ubiquitously distributed opportunistic pathogen that inhabits soil and water as well as animal-, human-, and plant-host-associated environments. The ubiquity would be attributed to its very versatile energy metabolism. P. aeruginosa has a highly branched respiratory chain terminated by multiple terminal oxidases and denitrification enzymes. Five terminal oxidases for aerobic respiration have been identified in the P. aeruginosa cells. Three of them, the cbb3-1 oxidase, the cbb3-2 oxidase, and the aa3 oxidase, are cytochrome c oxidases and the other two, the bo3 oxidase and the cyanide-insensitive oxidase, are quinol oxidases. Each oxidase has a specific affinity for oxygen, efficiency of energy coupling, and tolerance to various stresses such as cyanide and reactive nitrogen species. These terminal oxidases are used differentially according to the environmental conditions. P. aeruginosa also has a complete set of the denitrification enzymes that reduce nitrate to molecular nitrogen via nitrite, nitric oxide (NO), and nitrous oxide. These nitrogen oxides function as alternative electron acceptors and enable P. aeruginosa to grow under anaerobic conditions. One of the denitrification enzymes, NO reductase, is also expected to function for detoxification of NO produced by the host immune defense system. The control of the expression of these aerobic and anaerobic respiratory enzymes would contribute to the adaptation of P. aeruginosa to a wide range of environmental conditions including in the infected hosts. Characteristics of these respiratory enzymes and the regulatory system that controls the expression of the respiratory genes in the P. aeruginosa cells are overviewed in this article.